The Benzothiazine Core as a Novel Motif for DNA-Binding Small Molecules - Milena Mlakić; Ivona Čipor; Petra Kovačec; Goran Kragol; Ana Ratković; Tatjana Kovačević; Rahela Zadravec; Valentina Milašinović; Krešimir Molčanov; Ivo Piantanida; Irena Škorić (Molecules, 2023)
A new series of 4H-1,3-benzothiazine dyes were prepared and fully characterized in an aqueous medium. Benzothiazine salts were synthesized either through the classical synthetic pathway using Buchwald–Hartwig amination or through economical and environmentally friendly electrochemical synthesis. The latest synthetic approach employs successful electrochemical intramolecular dehydrogenative cyclization of N-benzylbenzenecarbothioamides to form 4H-1,3-benzothiazines. 4H-1,3-Benzothiazines were evaluated as novel DNA/RNA probes. Through the use of several methods such as UV/vis spectrophotometric titrations, circular dichroism and thermal melting experiments, the binding of four benzothiazine-based molecules to polynucleotides was examined. Compounds 1 and 2 acted as DNA/RNA groove binders, thus suggesting the potential of these compounds as novel DNA/RNA probes. This is a proof-of-concept study and will be expanded to include SAR/QSAR studies.